Joint Innovative Research Agenda for The Arctic: Programs, Projects, Success Stories - Konstantin S. Zaikov; Lyubov A. Zarubina; Svetlana V. Popkova; Nikita M. Kuprikov; Mikhail Yu. Kuprikov; Daniil A. Kvon; Leonid P. Ponyaev (Sustainability, 2021)
In the context of circumpolar international cooperation within the framework of the Joint Innovative Research Agenda, for the development of a systems approach, it is important to use the resources of existing platforms for multi-level mutually beneficial cooperation. The Council of Barents/Euro-Arctic Region and the University of the Arctic are unique examples of interaction and cooperation between the regions of the Arctic states. The Northern Dimension policy is also an important platform for such cooperation between Russia, the European Union, Iceland and Norway. Cross-border cooperation is integral to international relations, which stimulates the sustainable development of regions, creates growth points for innovative projects, and is focused on the evolution of international economic relationship. Universities and research institutes, as holders of expertise, and centers for studying good world practices and transferring excellence, occupy leading positions in the development of advanced ecosystems and the use of complex technologies, the training of highly qualified personnel for the Arctic, the creating of end-to-end digital technologies, the transforming of priority sectors of the states’ economies, and in the social sphere. This article discusses international project activities as one of the most effective tools contributing to the development of these issues. The authors provide examples of successful practices aimed at solving common challenges in the Arctic region, and conclude that “Arctic fever”, and the intensification of Arctic scientific partnerships through programs to support the introduction of technologies and innovations and the advancement of scientific stations in the Arctic, directly affect the development of local territories, give impetus to economic progress, and create new models of cooperation.